Short-term outcomes of tablet/smartphone-based (OBEST) application among obese Thai school-aged children and adolescents: A randomized controlled trial - Narueporn Likhitweerawong (2020)
© 2020 Elsevier Ltd Aims: Treatment of childhood and adolescent obesity is challenging. Smartphone applications have been widely used as a modality of obesity treatment. The study aimed to evaluate the effectiveness of tablet/smartphone-based (OBEST) application added to standard treatment of obesity. Methods: A randomized controlled trial was conducted in 77 obese children aged 10–15 years old from hospital-based and school-based settings. Participants were randomly assigned either the OBEST group or standard care group. After two months of treatment, both groups were assessed for anthropometric measurements, psychosocial functioning, and healthy eating behaviors and physical activities questionnaires. Results: Mean body mass index (BMI) was reduced significantly by 0.56 kg/m2 from baseline to two-month follow-up in the OBEST group (P =.005). Peer relationship problem scores from SDQ were significantly different between two groups (P =.049). All healthy eating behaviors and physical activities were no significant differences between groups and within-group, except for milk consumption every day observed in within-group of the OBEST application (p = 0.04). Conclusions: Using the OBEST application added to standard treatment might improve the effectiveness of obesity treatment in Thai children and adolescents. Future studies should be investigated outcomes in the longer periods and examined the potential factors related to outcomes.